1984
DOI: 10.1016/0378-5173(84)90180-7
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative approach to the determination of drug release from reverse-phase evaporation lipid vesicles. The influence of sodium ion-pair formation on warfarin partitioning and permeability

Abstract: SummaryThe influence of sodium ion-pair formation on warfarin partitioning and permeability has been investi~ted using reverse-phase evaporation lipid vesicles. An experimental method for the isolation of the vesicles having known amounts of encapsulated drug has been described. The partitioning of warfarin between phospholipid membrane and aqueous phase at different Na' concentrations was determined in separate experiments. Thus, using a two-compartment cylinder assembly the influence of Na+ concentration on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The authors explained this correlation to be driven by an ion-pairing mechanism, in particular between the deprotonated form of warfarin and sodium ions, which facilitates the passive diffusion of charged warfarin species across the membrane. The importance of the formation of the sodium ion-pairing of the deprotonated open side chain form of warfarin for membrane permeation was also suggested by Cools and Janssen after studying the effect on sodium ion concentration on permeation of warfarin across reverse-phase evaporation (REV) lipid vesicles of dipalmitoylphosphatidylcholine (DPPC) at pH 11.5. Although the authors in a previous paper had reported the importance of sodium ion concentration for warfarin–membrane permeation, the later study involving DPPC REVs demonstrated no clear correlation.…”
Section: Introductionmentioning
confidence: 91%
“…The authors explained this correlation to be driven by an ion-pairing mechanism, in particular between the deprotonated form of warfarin and sodium ions, which facilitates the passive diffusion of charged warfarin species across the membrane. The importance of the formation of the sodium ion-pairing of the deprotonated open side chain form of warfarin for membrane permeation was also suggested by Cools and Janssen after studying the effect on sodium ion concentration on permeation of warfarin across reverse-phase evaporation (REV) lipid vesicles of dipalmitoylphosphatidylcholine (DPPC) at pH 11.5. Although the authors in a previous paper had reported the importance of sodium ion concentration for warfarin–membrane permeation, the later study involving DPPC REVs demonstrated no clear correlation.…”
Section: Introductionmentioning
confidence: 91%